Prospek Obligasi Daerah Sebagai Alternatif Pembiayaan Pembangunan - Edy Suandi Hamid (Universitas Islam Indonesia, 2003)
One of the revenues sources can be used by regional government for spending its development budget is by selling local government bond. This is possible after government implemented Law No. 22/1999 and Law No. 25/1999 in 2001. Event though, up to now there is no clear central government regulation about local government bond, however in the future local government bond can potencial source for regional government, which lack of fund for her spending. In order to support action for selling local government bond, the regional government should create the debt management unit to manage this bond professionally.Keywords: revenue resources, local government bond, debt management unit.